Identifying differences between those with suicidal ideation-with-action, compared to ideation alone, using a community representative sample - Christine Chan; Walter Wodchis; Paul Kurdyak; Peter Donnelly (PLoS ONE, 2025)
Background Few studies examine suicidal ideation in the general population and who might act on suicidal thoughts. It is important to understand ideators, the largest group on the suicidality continuum. Objectives This study examines factors associated with suicidal ideation among community-dwelling individuals, and sociodemographic, health and help-seeking factors associated with ideation accompanied by planning or suicide attempt (‘ideation-with-action’) compared to ideation alone. Methods Using the 2002 and 2012 Canadian Community Health Surveys – Mental Health cycles (CCHS-MH), this cross-sectional cohort study examined 14,708 Ontarians 15 years and older who answered questions about suicidal ideation, and compared characteristics between non-ideators, ideators with a plan or previous attempt, and ideators alone, with chi-square tests and logistic regression. Results 2.1% of CCHS respondents reported past-year ideation alone (n = 302) and another 0.5% reported ideation with plan or past-year suicide attempt (n = 76). The risk profile of ideators compared to non-ideators was similar to that of ideators-with-action compared to ideators-without-action: male, younger, unpartnered, less educated, have lower income, no job, have a mood and anxiety disorder, a substance use disorder and seek help for mental health problems. Most ideators (65%) do not seek help, and those with a plan or previous suicide attempt are more likely to do so. Conclusion Ideators differ in profile in terms of whether they have ideation only, have made a plan or had previous attempts. Risk factors differentiating ideators from non-ideators are the same factors that further differentiate ideators-with-action compared to those with only ideation, suggesting the existence of a suicidality continuum and opening up the opportunity for targeting common risk factors in prevention efforts.